2020
DOI: 10.1177/1753466620933508
|View full text |Cite
|
Sign up to set email alerts
|

Lung under attack by COVID-19-induced cytokine storm: pathogenic mechanisms and therapeutic implications

Abstract: The lung is a key target of the cytokine storm that can be triggered by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), responsible for the widespread clinical syndrome known as coronavirus disease 2019 (COVID-19). Indeed, in some patients, SARS-CoV-2 promotes a dysfunctional immune response that dysregulates the cytokine secretory pattern. Hypercytokinemia underlies the hyperinflammatory state leading to injury of alveolar epithelial cells and vascular endothelial cells, as well as to lung infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 54 publications
1
111
0
6
Order By: Relevance
“…In fact, several studies found a clear relationship between the hyper-inflammatory state and the severity of the disease [6] , [7] , [8] , [9] . The pharmacological approach for treating ARDS needs of novel anti-inflammatory reagents as different COVID-19 patients might respond differently to these treatments [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies found a clear relationship between the hyper-inflammatory state and the severity of the disease [6] , [7] , [8] , [9] . The pharmacological approach for treating ARDS needs of novel anti-inflammatory reagents as different COVID-19 patients might respond differently to these treatments [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that even if the endothelial layer is not infected the cell integrity gets disturbed, most likely by cytokines released by macrophages. In this respect, it is known that high cytokine/interferon levels can induce the disruption of the alveolar barrier function (Broggi et al, 2020;Gustafson et al, 2020;Pelaia et al, 2020).…”
Section: Sars-cov-2 Disrupts the Alveolar Barrier Within The Alveolusmentioning
confidence: 99%
“…When the immune system generates an effective adaptive response against SARS-CoV-2, the infection can be eliminated and clinical manifestations are absent or may completely disappear [39]. A successful antiviral response is dependent on the expression of type I interferons (IFNs) [40][41][42] and on the activation of T lymphocytes (TCD4 + helper cells (Th) and TCD8 + cytotoxic cells), as well as specific antibody-producing B lymphocytes.…”
Section: Endothelial Cells In Sars-cov-2 Infection: Inflammation and mentioning
confidence: 99%
“…If the host organism does not develop an adequate adaptive immune response, the prolongation and amplification of innate mechanisms, combined with dysfunctional adaptive responses, lead to a hyperinflammatory state. The resulting intense and continuous release of proinflammatory cytokines underlies the cytokine storm [39] that is characteristic of acute respiratory distress syndrome (ARDS) [39][40][41][42], and is responsible for lung damage [39]. Patients with severe COVID-19 have decreased IFN production, as well as aberrant polarization of Th cells (predominantly Th17), increased expression of exhaustion-related surface markers, such as TIM3 and PD-1, and changes in the pattern of cytokine secretion [39,42,43] (Figure 1).…”
Section: Endothelial Cells In Sars-cov-2 Infection: Inflammation and mentioning
confidence: 99%
See 1 more Smart Citation